#Lanjutkandikamu: Al-Qur’an sebagai Teks Fungsional-Transformatif dalam Gerakan Filantropi Virtual - Muhammad Agil Atoillah; Nuzlin Nashihatul Ulayya; M. Yusuf; Muhammad Irham Saryulis (Dialogia, 2026)
This study examines the evolving landscape of Islamic philanthropy within virtual spaces, analyzing how the YouTube channel Hobby Makan transforms digital content into a strategic platform for empowering marginalized MSME communities in Indonesia through the #Lanjutkandikamu movement. Employing digital field research with a qualitative-descriptive approach, the study analyzes 11 purposively selected videos from 2019 to 2025 through two complementary theoretical frameworks: Ahmad Rafiq's Living Qur'an typology, which maps the social function of Qur'anic reception, and Asy-Sya'rāwī's Tafsir Khawāṭir, which provides the exegetical lens for interpreting the specific verses cited. The findings reveal that Hobby Makan's Qur'anic reception operates across three distinct yet interdependent layers: the Lived Qur'an, in which Qur'anic moral values are already embodied in the merchant’s cultural habitus and sanctified through editorial verse selection; the Living Qur'an, in which Evan and Tiwi function as deliberative scriptural agents who mobilize verses such as QS. Al-Baqarah [2]: 245 (Qarḍan Ḥasanan) and QS. Al-Mā’idah [5]: 2 (Ta’āwun) as a theological justification for collective philanthropic action; and the Propagating Qur'an, an extension of Rafiq's typology proposed by this study, in which algorithmically distributed Qur'anic citations reproduce themselves as collective social norms inviting audience imitation. The analysis further identifies a consistent curatorial logic in the channel's verse selection and critically examines the structural tension between altruistic sincerity and the monetized nature of digital content. This study concludes that the Qur'an in the Hobby Makan ecosystem functions as a functional-transformative text, an instrument that simultaneously sacralizes individual action, mobilizes collective giving, and constructs a virtual ummah bound by shared Qur'anic norms, thereby contributing a replicable model to the discourse on digital Islamic anthropology.